On the NOTION OF CIVIL-LEGAL REGIME OF UNAUTHORIZED CONSTRUCTION - V. V. Selivanov (Russian Journal of Economics and Law, 2011)
Construction of new real estate objects, reconstruction of the completed dwelling houses and other constructions causes the problem of legalization of the unauthorized real estate objects. The article is devoted to the research of the civil-legal nature of the unauthorized construction regime. The research is based on the author's view on «unauthorized construction» category. The notions «regime», «legal regime», «legal regime of the civil law objects» are analyzed, the notion of the civil-legal regime of unauthorized construction is formed, the mechanism of normative fixation of the civil-legal regime of unauthorized construction is defined, its legal nature is revealed.